Volume 7B: Structures and Dynamics 2013
DOI: 10.1115/gt2013-94594
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Catcher Bearing Model and an Explanation of the Forward Whirl/Whip Phenomenon Observed in Active Magnetic Bearing Transient Drop Experiments

Abstract: Though many approaches have been proposed in the literature to model the reaction forces in a catcher bearing (CB), there are still phenomena observed in experimental tests that cannot be explained by existing models. The following paper presents a novel approach to model a CB system. Some of the elements in the model have been previously introduced in the literature; however, there are other elements in the proposed model that are new, providing an explanation for the forward whirling phenomena that has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Vertically dropped rotors were studied in references [3,4,5,6,7]. The gravity does not lead to stable motion and the rotor is more able to develop 15 a forward whirl motion, as explained by Wilkes et al [8]. The forward whirl motion is frequency-limited and this is consistent with many of the previous studies concerning the rotor-stator interaction, see references [9, 10,11,12,13].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Vertically dropped rotors were studied in references [3,4,5,6,7]. The gravity does not lead to stable motion and the rotor is more able to develop 15 a forward whirl motion, as explained by Wilkes et al [8]. The forward whirl motion is frequency-limited and this is consistent with many of the previous studies concerning the rotor-stator interaction, see references [9, 10,11,12,13].…”
Section: Introductionsupporting
confidence: 70%
“…Sometimes a cross-coupled stiffness term opposed to the outer race whirling 210 motion is applied to counteract rotor whirl, see references [7,8].…”
Section: The Generalized Dahl Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…where x i contains the coordinates of the inner race center of gravity, M i is the inner race mass matrix, C i is the inner race damping matrix, P is the weight force of the inner race, and the vector F is the sum of the radial forces acting on the bearing inner race (see also Figure 7): F io is the interaction force on the inner race exerted by the rolling elements, F ir is the contact force exchanged between the inner race and the rotor during the contact (including a normal F rN component and a tangential one F fr ; see (15)), and F rub is the resultant force generated during the axial rub between the thrust surface of the bearing inner race and the lateral surface of the rotor sleeve (see (19)). Equation (8) describes the rotational dynamics of the bearing inner race:Ω…”
Section: Auxiliary Bearing Modelmentioning
confidence: 99%
“…Other researchers like J. Wilkes et al [19] observed strong circular forward whirl following an AMB failure and developed specific models to reproduce such phenomenon. They developed an innovative model of auxiliary bearing system that represents a great step forward in the reproduction of rotor-dynamic system behavior; in fact the model allows reproducing the forward whirl rotor orbit observed during International Journal of Rotating Machinery the landing tests.…”
Section: Introductionmentioning
confidence: 99%